Epigenetic Modifiers Revamp Secondary Metabolite Production in Endophytic Nigrospora sphaerica - Ramesha, Kolathuru Puttamadaiah; Chandra Mohana, Nagabhushana; Chandra Nayaka, Siddaiah; Satish, Sreedharamurthy (Frontiers in Microbiology, 2021)
During plant interaction, endophytes provide benefits to the host plant. Endophytes also contribute a variety of structural characteristics with biological potential. Nigrospora sphaerica, which produces phomalactone from Adiantum philippense L., was subjected to epigenetic modification. HPLC and GCMS analysis were used to determine secondary metabolite profiling. Epigenetic modifiers like DNA Methyltransferase (DNMT) and Histone deacetylase (HDAC) inhibitors increased the expression of biosynthetic pathways. The activation of new metabolites was observed as a result of the activation of cryptic biosynthetic gene clusters, as well as the silencing of phomalactone in some treatments. When compared to DNMT treatments, HDAC treatments showed a significant increase in cryptic metabolite induction. The induction of cryptic metabolites with biological significance by HDAC treatment is supported by our findings.